Application of Pocket Media Letters Against Fine Language And Motor Ability In Early Childhood - Afnita, Juli; Putro, Khamim Zarkasih; Naimah, Naimah; Rohinah, Rohinah (THUFULA, 2022)
The purpose of this study was to describe the application of letter pocket media to the language skills and fine motor skills of children at the build Peureulak State Kindergarten. This research is a descriptive qualitative type with data collection techniques of observation, interviews and documentation. Researchers made observations at the build Peureulak State Kindergarten with the research subjects there were 10 children aged 5-6 years and 6 teachers at the Peureulak Pembina State Kindergarten. The results showed that pocket letter media could improve children's language skills and fine motor skills.